The role of human ankle plantar flexor muscle-tendon interaction and architecture in maximal vertical jumping examined in vivo - Farris, D. J.; Lichtwark, G. A.; Brown, N. A. T.; Cresswell, A. G. (The Journal of Experimental Biology, 2016)
Humans utilise elastic tendons of lower limb muscles to store and return energy during walking, running and jumping. Anuran and insect species use skeletal structures and/or dynamics in conjunction with similarly compliant structures to amplify muscle power output during jumping. We sought to examine whether human jumpers use similar mechanisms to aid elastic energy usage in the plantar flexor muscles during maximal vertical jumping. Ten male athletes performed maximal vertical squat jumps. Three-dimensional motion capture and a musculoskeletal model were used to determine lower limb kinematics that were combined with ground reaction force data in an inverse dynamics analysis. B-mode ultrasound imaging of the lateral gastrocnemius (GAS) and soleus (SOL) muscles was used to measure muscle fascicle lengths and pennation angles during jumping. Our results highlighted that both GAS and SOL utilised stretch and recoil of their series elastic elements (SEEs) in a catapult-like fashion, which likely serves to maximise ankle joint power. The resistance of supporting of body weight allowed initial stretch of both GAS and SOL SEEs. A proximal-to-distal sequence of joint moments and decreasing effective mechanical advantage early in the extension phase of the jumping movement were observed. This facilitated a further stretch of the SEE of the biarticular GAS and delayed recoil of the SOL SEE. However, effective mechanical advantage did not increase late in the jump to aid recoil of elastic tissues.